Varied response of detoxification enzyme activities against lethal and sublethal exposures of phosphine in Tribolium castaneum populations - SINGH, SATYAPRIYA; TARIA, SUKUMAR; GAMBHIR, SUBHAM; SUBRAMANIAN, SABTHARISHI (The Indian Journal of Agricultural Sciences, 2023)
Resistance to phosphine fumigation in stored insects continues to be challenging in managing these pests worldwide. The role of detoxification enzymes in metabolizing phosphine is yet to be explored fully. The dose-response mortality against phosphine was assessed in this study from six field populations of Tribolium castaneum (Herbst) collected across India during 2021–23 at the Division of Entomology, ICAR-Indian Agricultural Research Institute, New Delhi. Further, the strength of Glutathione-S-Transferase (GST) and Cytochrome P450 monooxygenase (CYPs) was estimated at sublethal (LC30) and median lethal concentration (LC50). Dose-response probit assay found that the LC30 and LC50 values ranged from 0.018 to 0.363 and 0.038 to 1.277 mg/L, respectively. Our result showed that MZ (Mirzapur) and KA (Kailashahar) were the high and least resistant phosphine populations compared to the susceptible reference LS (lab population). The magnitude of GST and CYPs activities in resistant populations were more elevated than in susceptible populations. Our study found that the enhancement of GST and CYPs activity was eight and nine-fold and two and three-fold at LC30 and LC50 concentrations, respectively. Correlation analysis revealed a significant positive association between GST (r=0.94, P